Political and Legal Presuppositions for the Comprehensive Repair of Victims of Forced Displacement in Colombia as a Result of the Armed Conflict - Elber Moreno Hurtado; Wilber Alvarez Sierra (Via Inveniendi Et Iudicandi, 2017)
In this article, you will found those political and legal issues about the victims reparation in Colombia, based on a transnational justice context, that is currently facing our country. Since 1960, aprox, the armed conflict in Colombia has been developed involving two main subjects, which are represented by the state through its public forces and rulers on one hand, and members of illegal armed groups on the other. Additionally, in this scenario are a few others that are not agree with the ideologies of armed conflict beginnings, which are perhaps, the most affected group: the civil population.